Islamic Humanism Education for the World - Sobry, M. (STKIP Yapis Dompu, 2022)
In this article the author tries to describe Islamic humanism education/humanist education. This conception is an offer against the restlessness and anxiety of Human in the conception of Western education as well as the actual offer of Islam and scholars for education, people, and the world. The conception of Humanist Education is based on the study of Islamic epistemology, namely